Conceptual Framework for Introducing e-Governance in Iraqi Higher Education Institutions - Ammar Ali Awad; Fatihallah Jaleel Mhwise (University of Thi-Qar Journal of Science, 2019)
With emergence of technology and growing demand of the society, e-Governance became a key issue and developed nations started adopting it to better serve their organizations through efficient and effective services, with accountability and transparency. e-governance can be defined as a set of activities involving the effective contribution of information and communication technology (ICT) for strengthening administration and management e-governance is the use of Information and Communication Technologies (ICT) for the planning, implementation, and monitoring of higher education programs, projects, and activities. The higher education sector has remarkable growth in the administration of institutions intricate. Many paperes reveal that the integration of ICT helps to reduce the intricacy and enhance the overall administration of higher education. e-Governance is expected to help deliver cost-effective and easy-to-access user services, and improve processing of transactions. . The Iraqi higher education system has declined somewhat over the past three decades due to remarkable increase in the number of colleges and universities and their privatization. It has become very important for the government to keep track of their functioning. Educational institutions may have various requirements that include computerization and management of processes such as registration, admission, student information, classes, time table, transport, attendance, library, salary and expenses, examinations, performance, grades, hostels, security and reports. In this paper, an attempt have been made to discuss the concept of e-governance and use of latest application in higher education sector. This study also propose a roadmap to the implementation of an e-governance framework for monitoring, regulating and better administration in Iraqi higher education system.